SISTEM INFORMASI PEMESANAN MENU MAKANAN BERBASIS WEB - Sri Rejeki; Khairunisa Fadhilla Ramdhania; Kusdarnowo Hantoro (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
AbstractThe consumer's need for information technology is essential. The need for information that can help make it easier for humans to work. The advantage of technology for the culinary business is the creation of a web-based food menu ordering information system design, then delivered to the customer's address. The system development method used is the waterfall model. System design uses UML, the system is built using the programming language PHP, Javascript with MySQL database, on system testing with Blackbox Testing. This paper discusses the menu ordering information system with the aim of making it easier for consumers to place orders at Mr. Kusworo's Seafood, with the aim of research building a website on menu ordering, with this web-based information system application it can inform the available menus so that it can simplify menu ordering, help customers, and is more efficient in making payments and makes it easier for employees to view income data.Â Keywords: information systems, food menu ordering, waterfall, UML, PHP, Javascript, MySQL.